Civilizations in conflict : Byzantium, Islam, and the Crusades - Sitko, Joseph (Colorado : Chariot Productions [production company] ; Illinois : United Learning [distributor])
This program focuses on certain key historical events taking place in the southern and eastern portions of the old Roman Empire during the ten centuries after the fall of Rome
Editor, Joseph Sitko
Narrator: Lois La Fond
Keywords: Rome -- Civilization; Rome -- History; Rome -- Historiography